RPPanalyzer Toolbox: An improved R package for analysis of reverse phase protein array data. (September 2014) - von der Heyde, Silvia; Sonntag, Johanna; Kaschek, Daniel; Bender, Christian; Bues, Johannes; Wachter, Astrid; Timmer, Jens; Korf, Ulrike; Beißbarth, Tim
Analysis of large-scale proteomic data sets requires specialized software tools, tailored toward the requirements of individual approaches. Here we introduce an extension of an open-source software solution for analyzing reverse phase protein array (RPPA) data. The R package RPPanalyzer was designed for data preprocessing followed by basic statistical analyses and proteomic data visualization. In this update, we merged relevant data preprocessing steps into a single user-friendly function and included a new method for background noise correction as well as new methods for noise estimation and averaging of replicates to transform data in such a way that they can be used as input for a new time course plotting function. We demonstrate the robustness of our enhanced RPPanalyzer platform by analyzing longitudinal RPPA data of MET receptor signaling upon stimulation with different hepatocyte growth factor concentrations.